2007
DOI: 10.1111/j.1445-2197.2007.04065.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Stimulation in Thyroid Surgery: Is It Really Useful?

Abstract: Use of a nerve stimulator did not aid in anatomical dissection of the RLN and was useful in identifying only one EBSLN. Discontinuous nerve monitoring by stimulation during total thyroidectomy confers no obvious benefit for the experienced surgeon in nerve identification, functional testing or injury prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 16 publications
(30 reference statements)
2
58
0
5
Order By: Relevance
“…Similarly in our study, while there was no significant difference between the two groups in terms of RLN paralysis, the duration of operation in the group with nerve monitoring was significantly shorter. Even though some studies report that nerve dissection using IONM reduces the rate of permanent nerve damage following surgery [11][12][13][14], there is no consensus on this subject [15][16][17]. As the results of our study support us, we clinically suppose that nerve monitoring does not provide any contribution to an experienced surgeon; however, it might be used to assist less experienced surgeons with anatomical identification.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly in our study, while there was no significant difference between the two groups in terms of RLN paralysis, the duration of operation in the group with nerve monitoring was significantly shorter. Even though some studies report that nerve dissection using IONM reduces the rate of permanent nerve damage following surgery [11][12][13][14], there is no consensus on this subject [15][16][17]. As the results of our study support us, we clinically suppose that nerve monitoring does not provide any contribution to an experienced surgeon; however, it might be used to assist less experienced surgeons with anatomical identification.…”
Section: Discussionsupporting
confidence: 75%
“…During surgery, methods such as the palpation of cricothyroid muscle synchronous with the nerve impulse, observation of the movement of vocal cords by using direct or fiberoptic nasopharyngoscopy, measurement of the pressure on the endotracheal tube exerted by the movement of vocal cords, placement of electrodes on the vocal cord muscles, and formation of contact between the vocal cord mucosa and the electrodes placed on the surface of the endotracheal tube are performed [7][8][9][10]. Whereas in some studies, it has been reported that nerve dissection using intraoperative nerve monitoring (IONM) reduces the rate of permanent nerve damage following surgery [11][12][13][14], there is no consensus on this subject [15][16][17]. This study aims to compare and contrast the effects of two different technical approaches-visual identification of RLN combined with IONM and no RLN identification-on RLN damage in total thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Pagedar and Freeman (34) reviewed the charts of 112 patients that underwent thyroidectomies with 178 poles dissected and found an identification rate of 98.3% without neural stimulation. In the prospective case series of LochWilkinson (35), 86% of the EBSLNs were seen in 50 total thyroidectomies and electrostimulation helped to find only 1 additional EBSLN.…”
Section: Intraoperative Ebsln Identification and The Role Of Ionmmentioning
confidence: 99%
“…Equipment and consumables for IONM, especially CIONM, are expensive and very country-specific. The IONM technique can hardly be cost-effective when only the direct costs of RLN injuries are considered (55). To be cost-effective, all indirect costs of RLN injuries, including speech therapy, repeat laryngeal examinations, VF surgery, and legal claims, must be factored into the costeffectiveness equation.…”
Section: Cost-effectiveness Of Ionm: An Economic Challengementioning
confidence: 99%